Endometrial hyperplasia and tubal ectopic: a correlation - Gainder, Shalini; Kaushal, Aayushi; Aggarwal, Aleena; Sharma, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Anovulation due to polycystic ovarian syndrome (PCOS) is one of the causes of endometrial hyperplasia in infertile women. Tubal ectopic apart from tubal factors can also be the result of hampered endometrial receptivity in these women which could be due to disturbed hormonal mileu, endometrial hyperplasia at cornua thereby interfering with transport of embryo from fallopian tube to uterus, or could be because of mechanical damage caused while taking endometrial biopsy. We are presenting case series of eight women of PCOS who presented to infertility clinic within two years with history of ectopic pregnancy or had subsequent ectopic pregnancy (after taking endometrial biopsy) with histopathology report of endometrial hyperplasia with or without atypia were enrolled. Out of 1200 PCOS women presenting to infertility clinic, eight women had coexistence of both endometrial hyperplasias and ectopic pregnancy. It is rare to find endometrial hyperplasias causing ectopic pregnancy. The causative factor in these cases could be the faulty endometrium by not being receptive thereby causing the embryo to implant in the fallopian tube or the tubes due to subtle infection secondary to repeated endometrial evaluation.